Development of a low-cost PV system using an improved INC algorithm and a PV panel Proteus model - Motahhir, Saad; Chalh, Abdelilah; El Ghzizal, Abdelaziz; Derouich, Aziz (Journal of cleaner production, 2018)
This paper proposes a photovoltaic (PV) model for the design of PV systems with a simple MPPT to achieve high efficiency, faster response and low cost. First, a PV panel model is developed using SPICE code in Proteus tool. The verification and the validation are performed via an experimental test bench. Afterwards, a new modified Incremental Conductance (INC) algorithm is introduced. The proposed algorithm avoids the high number of the mathematical divisions used in the conventional INC. Both methods are implemented in the low-cost Arduino Uno board using the simulated PV panel model. The results show that the modified method presents good performances regarding response time (0.1 s), steady-state oscillation, and efficiency (98.5%). To validate the proposed system, a hardware testbench is implemented using the low-cost ATMega328 microcontroller in the Arduino Uno board. Substantial cost reduction has been attained proving the financial competitiveness of the proposed controller.